The Impact of Multipollutant Clusters on the Association Between Fine Particulate Air Pollution and Microvascular Function. Issue 2 (March 2016) - Ljungman, Petter L.; Wilker, Elissa H.; Rice, Mary B.; Austin, Elena; Schwartz, Joel; Gold, Diane R.; Koutrakis, Petros; Benjamin, Emelia J.; Vita, Joseph A.; Mitchell, Gary F.; Vasan, Ramachandran S.; Hamburg, Naomi M.; et al.
Abstract : Background: Prior studies including the Framingham Heart Study have suggested associations between single components of air pollution and vascular function; however, underlying mixtures of air pollution may have distinct associations with vascular function. Methods: We used a k-means approach to construct five distinct pollution mixtures from elemental analyses of particle filters, air pollution monitoring data, and meteorology. Exposure was modeled as an interaction between fine particle mass (PM2.5 ), and concurrent pollution cluster. Outcome variables were two measures of microvascular function in the fingertip in the Framingham Offspring and Third Generation cohorts from 2003 to 2008. Results: In 1, 720 participants, associations between PM2.5 and baseline pulse amplitude tonometry differed by air pollution cluster (interaction P value 0.009). Higher PM2.5 on days with low mass concentrations but high proportion of ultrafine particles from traffic was associated with 18% (95% confidence interval: 4.6%, 33%) higher baseline pulse amplitude per 5 μg/m 3 and days with high contributions of oil and wood combustion with 16% (95% confidence interval: 0.2%, 34%) higher baseline pulse amplitude. We observed no variation in associations of PM2.5 with hyperemic response to ischemia observed across air pollution clusters. Conclusions: PM2.5 exposure from air pollution mixtures with large contributions of local ultrafine particles from traffic, heating oil, and wood combustion was associated with higher baseline pulse amplitude but not hyperemic response. Our findings suggest little association between acute exposure to air pollution clusters reflective of select sources and hyperemic response to ischemia, but possible associations with excessive small artery pulsatility with potentially deleterious microvascular consequences. Abstract : Supplemental Digital Content is available in the text.